Targeting Epidermal Growth Factor Receptor in triple negative breast cancer: New discoveries and practical insights for drug development. (February 2017) - Costa, Ricardo; Shah, Ami N.; Santa-Maria, Cesar A.; Cruz, Marcelo R.; Mahalingam, Devalingam; Carneiro, Benedito A.; Chae, Young Kwang; Cristofanilli, Massimo; Gradishar, William J.; Giles, Francis J.
Highlights: EGFR is commonly expressed in triple negative breast cancer. Monoclonal antibodies targeting EGFR failed to show significant activity. Pre-clinical data support interaction between EGFR and MET receptor. Data on EGFR signaling pathway and immune checkpoints is scarce. Abstract: Triple negative breast cancer (TNBC) accounts for 10–20% of cases in breast cancer. Despite recent advances in the treatment of hormonal receptor+ and HER2+ breast cancers, there are no targeted therapies available for TNBC. Evidence supports that most patients with TNBC express the transmembrane Epidermal Growth Factor Receptor (EGFR). However, early phase clinical trials failed to demonstrate significant activity of EGFR-targeted monoclonal antibodies and/or tyrosine kinase inhibitors. Here, we review the recent discoveries related to the underlying biology of the EGFR pathway in TNBC, clinical progress to date and suggest rational future approaches for investigational therapies in TNBC.